2014
DOI: 10.1097/pas.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CIC-FOXO4 Gene Fusion in Undifferentiated Small Round Cell Sarcoma

Abstract: Differential diagnosis of small round cell sarcomas (SRCSs) grouped under the Ewing sarcoma family of tumors (ESFT) can be a challenging situation for pathologists. Recent studies have revealed that some groups of Ewing-like sarcoma show typical ESFT morphology but lack any EWSR1-ETS gene fusions. Here we identified a novel gene fusion, CIC-FOXO4, in a case of Ewing-like sarcoma with a t(X;19)(q13;q13.3) translocation. The patient was a 63-year-old man who had an asymptomatic, 30-mm, well-demarcated, intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 14 publications
4
111
1
1
Order By: Relevance
“…Recent studies have identified that some of these cases carry translocations involving BCOR-CCNB3 (28-30), CIC-DUX4 (31, 32), or CIC-FOXO4 (33,34). These variants are genetically distinct from Ewing sarcoma and portend different prognoses, for example, with BCOR-CCNB3 tumors (28,29) showing good chemosensitivity, which must now be considered as distinct entities for treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified that some of these cases carry translocations involving BCOR-CCNB3 (28-30), CIC-DUX4 (31, 32), or CIC-FOXO4 (33,34). These variants are genetically distinct from Ewing sarcoma and portend different prognoses, for example, with BCOR-CCNB3 tumors (28,29) showing good chemosensitivity, which must now be considered as distinct entities for treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of CRS in the HN is extremely rare, only 11 cases being described to date [12,13,17,18,22,23,27]. As CRS is a relatively new pathologic entity, without a specific immunoprofile, it remains under-recognized outside specialist sarcoma centers.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-year overall survival (OS) rate for HN-CRS patients was 78%, while for HN-ES it was 100%. The OS of ES and CRS showed a trend toward a favorable and BCOR-related fusions involving CCNB3, MAML3, and ZC3H7B gene partners [11][12][13][14][15][16][17][18]. As most of the initial series have included a limited number of cases of each molecular subset, definitive classification of these tumors within or outside the more common ES spectrum has been difficult to establish.…”
Section: Translocation Cic-foxo4mentioning
confidence: 99%
“…Consistent with this, EWSR1-ETV1 and EWSR1-ETV4 fusions, which presumably function as aberrant versions of the transcription factors ETV1 and ETV4, respectively, have been observed in EFTs (Jeon et al 1995;Kaneko et al 1996). EFTs with CIC-FOXO4 fusions have also been reported (Sugita et al 2014;Solomon et al 2014). …”
Section: Cic-rearranged Ewing-like Sarcomasmentioning
confidence: 99%